2021
DOI: 10.1155/2021/8842062
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides of Sporoderm-Broken Spore of Ganoderma lucidum Modulate Adaptive Immune Function via Gut Microbiota Regulation

Abstract: Ganoderma lucidum (Leyss.Fr.) Karst is one of the well-known medicinal macrofungi all over the world, and mounting researches have focused on the polysaccharides derived from the spores of G. lucidum. In the present study, BALB/c mice (n = 8–10) were administered with crude polysaccharides of G. lucidum spores (CPGS) and the refined polysaccharides of G. lucidum spores (RPGS) for 30 days to investigate their effect on the adaptive immune system. Results showed that CPGS and RPGS displayed diverse effects on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The BPP treatment regulated gut microbiota functions, indicating that a high dose of BPP may impose potential and beneficial effects on human diseases by regulating the gut microbiota. In addition, the high dose of BPP obviously upregulated the genes that were responsible for lipid metabolism, nucleotide metabolism, membrane transport, translation, and xenobiotics biodegradation and metabolism ( p < 0.05), which is similar to previous reports [ 47 , 48 ], suggesting that BPP could regulate the metabolism of the gut microbiota. Collectively, functional predictions via Tax4Fun demonstrate that BPP may modulate the gut micrology by regulating those bacteria to change their metabolites and cellular processes.…”
Section: Resultssupporting
confidence: 88%
“…The BPP treatment regulated gut microbiota functions, indicating that a high dose of BPP may impose potential and beneficial effects on human diseases by regulating the gut microbiota. In addition, the high dose of BPP obviously upregulated the genes that were responsible for lipid metabolism, nucleotide metabolism, membrane transport, translation, and xenobiotics biodegradation and metabolism ( p < 0.05), which is similar to previous reports [ 47 , 48 ], suggesting that BPP could regulate the metabolism of the gut microbiota. Collectively, functional predictions via Tax4Fun demonstrate that BPP may modulate the gut micrology by regulating those bacteria to change their metabolites and cellular processes.…”
Section: Resultssupporting
confidence: 88%
“…Recent investigations have revealed that sugars and glycosides are important bioactive components in mushrooms, such as G. lucidum polysaccharides having antibacterial, 17 antitumor, 18 immunomodulatory, 19 and inflammation effects. 20 In this study, 19 sugars and 42 glycoside metabolites were identified in I. hispidus grown on five different tree species ( Table 2 ). The contents of sugars differ greatly among them, and the contents of cyclic adenosine diphosphate (ADP)-ribose, trehalose, fucose, and iditol in MA were higher than that in other I. hispidus samples .…”
Section: Resultsmentioning
confidence: 92%
“…Recent investigations have revealed that sugars and glycosides are important bioactive components in mushrooms, such as G. lucidum polysaccharides having antibacterial, antitumor, immunomodulatory, and inflammation effects . In this study, 19 sugars and 42 glycoside metabolites were identified in I.…”
Section: Resultsmentioning
confidence: 99%
“…Gut microbiota is necessary for immune homeostasis, and a healthy gut microbiota is important for the regulation of the host immune responses ( Belkaid and Harrison, 2017 ). In this study, certain microbiota with high abundance at genus level in D group are involvement with immune response, such as Faecalibacterium ( Yeoh et al, 2021 ), Desulfovibrionaceae ( Su et al, 2021 ), and Prevotella ( Larsen, 2017 ). It is reported that genus Prevotella could promote Ig A and Ig G response in sera and synovial fluids of arthritis patients ( Moen et al, 2003 ), and genus Faecalibacterium and Desulfovibrionaceae can take function in inflammation regulation ( Schneeberger et al, 2015 ; Chang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 97%